Stad-Type Cooperative Learning Design to Develop Student Online Learning Activities - Irna Sjafei (Peneliti.net, 2021)
This study is one of the ways to compile development research, namely the design stage. The research objective is to produce conceptual and procedural models and to identify components of online learning that apply the STAD (Student Team Achievement Division) type of cooperative learning method. The use of internet media in the form of social media can support online learning. Cooperative learning is an alternative to be applied using online learning. Use of social media online if designed properly will help active and fun learning. The design of cooperative learning using online is carried out in 6 (six) stages, namely the stage of conveying goals and motivating; deliver material, explore group work, conclude and reinforce, evaluate and award group stages